ANALYSIS OF FACTORS THAT AFFECT THE WORK PRODUCTIVITY OF EMPLOYEES OF PT. BANK PAPUA BRANCH OFFICE NABIRE REGENCY NABIRE PAPUA PROVINCE - Riko Gasmani, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The aim of this study is to determine the factors that affect the productivity of PT. Bank Papua Branch Office Nabire and to determine the factors that most affect the productivity of emplpyees of PT. Bank Papua Branch Office Nabire District Nabire Province Papua.This research was conducted at PT. Bank Papua Branch Office Nabire Province Papua. Population in this research is all employees of PT. Bank Papua Branch Office Nabire District Nabire with population of 105 people. Sampling technique using purposive sampling, so that can be sampling as many as 83 people. Analyzer use multiple regression analysis.The results showed the existence of education and training, mutation and work loyalty significantly affect the productivity of employees PT. Bank Papua Branch Office Nabire District Nabire. The result of regression test simultanne usly with F test shows F count equal to 57,920. These results show the variable used in the model synchron usly or together. This means that the variables of education and training, mutation, and work loyalty able to explain the variables of employee productivity. The R square 0,750 indicates the varian in education and training, mutation, and work loyalty can explain the variation employee productivity by 75 percent, while the cost of 25 percent is caused by other variables that can not be used in the research model.